DEVELOPING VISUAL NOVEL GAME WITH SPEECH-RECOGNITION INTERACTIVITY TO ENHANCE STUDENTS’ MASTERY ON ENGLISH EXPRESSIONS - Elizabeth Anggraeni Amalo; Imam Dui Agusalim; Citra Devi Murdaningtyas (Institut Teknologi Sepuluh Nopember, 2017)
The teaching of English-expressions has always been done through conversation samples in form of written texts, audio recordings, and videos. In the meantime, the development of computer-aided learning technology has made autonomous language learning possible. Game, as one of computer-aided learning technology products, can serve as a medium to provide educational contents like that of language teaching and learning. Visual Novel is considered as a conversational game that is suitable to be combined with English-expressions material. Unlike the other click-based interaction Visual Novel Games, the visual novel game in this research implements speech recognition as the interaction trigger. Hence, this paper aims at elaborating how visual novel games are utilized to deliver English-expressions with speech recognition command for the interaction. This research used Research and Development (R&D) method with Experimental design through control and experimental groups to measure its effectiveness in enhancing students’ English-expressions mastery. ANOVA was utilized to prove the significant differences between the control and experimental groups. It is expected that the result of this development and experiment can devote benefits to the English teaching and learning, especially on English-expressions.